2020
DOI: 10.1109/taslp.2020.2987748
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Based Spatial Soundfield Reproduction Using an Irregular Loudspeaker Array

Abstract: Sound intensity is an acoustic quantity closely linked with human perception of sound location, and it can be controlled to create a high level of realism to humans in soundfield reproduction systems. In this paper, we present an intensity matching technique to optimally reproduce sound intensity over a continuous spatial region using an irregular loudspeaker array. This avoids several known limitations in the previous works on intensity based soundfield reproduction, such as a single sweet spot for the listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In [21], we have shown that accurate reconstruction of sound intensity guarantees a good localization perception within the target region by perceptual experiments. As the first objective performance measure, we define the relative error of sound intensity as…”
Section: Simulation Setup and Criteriamentioning
confidence: 93%
See 4 more Smart Citations
“…In [21], we have shown that accurate reconstruction of sound intensity guarantees a good localization perception within the target region by perceptual experiments. As the first objective performance measure, we define the relative error of sound intensity as…”
Section: Simulation Setup and Criteriamentioning
confidence: 93%
“…where N L is the number of loudspeakers. Note that here we assume incoherent superposition of loudspeaker signals [21].…”
Section: Reproduced Sound Intensitymentioning
confidence: 99%
See 3 more Smart Citations